Five Steps to Inject Transformative Change into the Post-2020 Global Biodiversity Framework - Grumbine, R. Edward; Xu, J.C. (Oxford University Press, 2021)
Accelerating declines in biodiversity and unmet targets in the Convention on Biological Diversity's 2010–2020 Strategic Plan for Biodiversity are stimulating widespread calls for transformative change. Such change includes societal transitions toward sustainability, as well as in specific content of the CBD's draft Post-2020 Global Biodiversity Framework. We summarize research on transformative change and its links to biodiversity conservation, and discuss how it may influence the work of the CBD. We identify five steps to inject transformative change into the design and implementation of a new post-2020 framework: Pay attention to lessons learned from transitions research, plan for climate change, reframe area-based conservation, scale up biodiversity mainstreaming, and increase resources. These actions will transform the very nature of work under the CBD; a convention based on voluntary implementation by countries and facilitated by international administrators and experts must now accommodate a broader range of participants including businesses, Indigenous peoples, and multiple nonstate actors.